Liquid Biopsy in EGFR-Mutated Advanced NSCLC from T790M to MET Amplification: Clinical Implications and Possibilities in the Resistance Setting - Luigi Della Gravara; Ciro Battiloro; Aniello Avellino; Francesca Caputo; Carmine D'Aniello; Danilo Rocco (MDPI AG, 2023)
According to the ESMO and ASCO clinical guidelines, the main role of liquid biopsy in EGFR+ advanced NSCLC patients is represented by T790M detection after erlotinib/gefitinib/afatinib progression. However, the general international expert consensus regards osimertinib as the preferred upfront treatment in this setting; therefore, this role has been scaled back in recent years. As of today, liquid biopsy has no ASCO or ESMO recommendation following first-line osimertinib; in the same vein, no targeted therapy has received ASCO or ESMO recommendation following post upfront Osimertinib progression. However, this standard could change in the near future. Therefore, adopting a clinical point of view, this paper aims to provide a comprehensive review on the previous, the current and the possible future role of liquid biopsy in the framework of the diagnostic-therapeutic algorithm of EGFR+ advanced NSCLC.